2008
DOI: 10.1154/1.2903738
|View full text |Cite
|
Sign up to set email alerts
|

Study of calcium oxalate monohydrate of kidney stones by X-ray diffraction

Abstract: X-ray powder diffraction was used to study the phase composition of human renal calculi. The stones were collected from 56 donors in Vitória, Espírito Santo state, southeastern Brazil. An XRD phase quantification revealed that 61% of the studied renal stones were composed exclusively of calcium oxalate ͓34% formed only by calcium oxalate monohydrate ͑COM͒ and 27% presents both monohydrate and dihydratate calcium oxalate͔. The 39% multi-composed calculi have various other phases such as uric acid and calcium ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Because of this, and together with the fact that calcium oxalate is frequently found as a biomineral in plants, research into the phases of calcium oxalate, including its hydrates, is attracting significant attention. [4][5][6][7][8][9][10][11][12][13][14] 4,6,[15][16][17][18][19][20] As in the case of calcium carbonate, an amorphous phase has also been detected for calcium oxalate, with a degree of hydration close to 1 molecule of water per formula unit. 21,22 On the other hand, understanding the structure and polymorphism of anhydrous calcium oxalate (COA) directly from experiment is a challenge due to the fact that it is highly hygroscopic and therefore little work has been done so far on these phases.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, and together with the fact that calcium oxalate is frequently found as a biomineral in plants, research into the phases of calcium oxalate, including its hydrates, is attracting significant attention. [4][5][6][7][8][9][10][11][12][13][14] 4,6,[15][16][17][18][19][20] As in the case of calcium carbonate, an amorphous phase has also been detected for calcium oxalate, with a degree of hydration close to 1 molecule of water per formula unit. 21,22 On the other hand, understanding the structure and polymorphism of anhydrous calcium oxalate (COA) directly from experiment is a challenge due to the fact that it is highly hygroscopic and therefore little work has been done so far on these phases.…”
Section: Introductionmentioning
confidence: 99%
“…The powder diffraction database was used for the phase identication, which revealed that the XRD patterns of all samples well matched with the COM phase (PDF 20-0231). 47 The identied peaks projected at d ¼ 5.83, 3.60, 2.94, 2.47, 2.33, 2.25, and 2.06Å corresponding to COM crystal, were assigned to (À101), (020), (À202), (112), (130), (202), (321) lattice planes, respectively. The doping of iron into the COM lattice did not create any new phase, conrming that iron occupied the interstitial position of COM crystals (Fig.…”
Section: X-ray Diffraction and Ft-ir Analysismentioning
confidence: 99%
“…With the development of x-ray powder profile-fitting structure refinement using the Rietveld method, 26-28 the quantitative estimates of mineral phases in urinary or PSs can now be accomplished with an increased accuracy. 12,13,29 This method also provides the microstructural features intrinsic to crystalline environment, e.g., grain size, microstrain, and preferred orientation. These factors are important when attempting to elucidate the mechanism for in vivo crystal growth.…”
Section: Introductionmentioning
confidence: 99%